Single event effects in aerospace - Petersen, Edward, 1932- (Piscataway, NJ : IEEE Press ; Hoboken, N.J. : Wiley, 2011)
"Enables readers to better understand, calculate, and manage single event effectsSingle event effects, caused by single ionizing particles that penetrate sensitive nodes within an electronic device, can lead to anything from annoying system responses to catastrophic system failures. As electronic components continue to become smaller and smaller due to advances in miniaturization, electronic components designed for avionics are increasingly susceptible to these single event phenomena. With this book in hand, readers learn the core concepts needed to understand, predict, and manage disruptive and potentially damaging single event effects. Setting the foundation, the book begins with a discussion of the radiation environments in space and in the atmosphere. Next, the book draws together and analyzes some thirty years of findings and best practices reported in the literature, exploring such critical topics as: Design of heavy ion and proton experiments to optimize the data needed for single event predictions; Data qualification and analysis, including multiple bit upset and parametric studies of device sensitivity; Pros and cons of different approaches to heavy ion, proton, and neutron rate predictions; Results of experiments that have tested space predictions. Single Event Effects in Aerospace is recommended for engineers who design or fabricate parts, subsystems, or systems used in avionics, missile, or satellite applications. It not only provides them with a current understanding of single event effects, it also enables them to predict single event rates in aerospace environments in order to make needed design adjustments."--Publisher's description.
17. Limitations of the IRPP Approach. 17.1 The IRPP and Deep Devices. 17.2 The RPP When Two Hits are Required. 17.3 The RPP Approaches Neglect Track Size. 17.4 The IRPP Calculates Number of Events, not Total Number of Upsets. 17.5 The RPP Approaches Neglect Effects that Arise Outside the Sensitive Volume. 17.6 The IRPP Approaches Assume that the Effect of Different Particles with the Same LET is Equivalent. 17.7 The IRPP Approaches Assume that the LET of the Particle is not Changing in the Sensitive Volume. 17.8 The IRPP Approach Assumes that the Charge Collection Does Not Change with Device Orientation. 17.9 The Status of Single Event Rate Analysis -- Appendix A Useful Numbers. Appendix B Reference Equations. Appendix C Quick Estimates of Upset Rates Using the Figure of Merit. Appendix D Part Characteristics. Appendix E Sources of Device Data.
Includes bibliographical references (pages 455-487) and indexes.
Keywords: Astrionics -- Protection; Electronic apparatus and appliances -- Effect of radiation on; Electromagnetic pulse; Astrionics; Electric apparatus and appliances -- Protection; Electronic apparatus and appliances -- Effect of radiation on; Electromagnetic pulse; TECHNOLOGY & ENGINEERING / Aeronautics & Astronautics; Electronic books